Attitudes Toward Transnational Surrogacy, Ambivalent Sexism, and Views on Financial Allocation. Issue 1 (2nd January 2023) - Hashim, Prianka H.; Michniewicz, Kenneth; Richmond, Kate
Abstract: In this exploratory study, we examine perceptions of commercial surrogacy and how these perceptions might influence decisions about how to allocate financial resources to those involved in the surrogacy market in a U.S. sample. We surveyed 340 participants through MTurk and students enrolled in psychology courses at Muhlenberg College on their perceptions of surrogacy and their decisions on how to allocate compensation. Findings indicate that the surrogate's marital status influenced financial allocations to parties involved in the surrogacy arrangement, and men and those high in hostile sexist attitudes offered less money to surrogates and more money to doctors. These findings support previous studies showing how ambivalent sexism influences attitudes toward reproduction.